2006
DOI: 10.2193/0091-7648(2006)34[675:sojlpi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Juvenile Lesser Prairie-Chickens in Kansas

Abstract: Juvenile survival has been identified as the most critical demographic parameter influencing grouse populations. Little information currently exists on survival of juvenile lesser prairie‐chickens (Tympanuchus pallidicinctus). We regularly flushed 51 individually identifiable lesser prairie‐chicken broods over a 6‐year period to estimate survival from hatch to 14 days post‐hatch (early period) and from 15 to 60 days post‐hatch (late period). Estimates of overall daily survival rates were 0.949 (95% C***I=0.932… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 31 publications
0
40
1
Order By: Relevance
“…Previous studies on wild‐hatched galliform chicks reported >70% of all mortalities occurred within the first 21 days posthatch, and greater than 80% of these were attributed to predation (Zwickel and Bendell , Riley et al , Pitman et al , Gregg et al , Manzer and Hannon ). The next most commonly reported mortality was from exposure, which was often not differentiated from malnutrition or starvation in these field studies.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies on wild‐hatched galliform chicks reported >70% of all mortalities occurred within the first 21 days posthatch, and greater than 80% of these were attributed to predation (Zwickel and Bendell , Riley et al , Pitman et al , Gregg et al , Manzer and Hannon ). The next most commonly reported mortality was from exposure, which was often not differentiated from malnutrition or starvation in these field studies.…”
Section: Discussionmentioning
confidence: 97%
“…Empirical estimates of the probability of juvenile survival are more likely to be <0.38 (Lesser Prairie-Chickens: 0.124, Pitman et al 2006;Greater Prairie-Chickens: 0.38, Wisdom and Mills 1997). Therefore, the Greater Prairie-Chicken population examined in this study is unlikely to be maintained by current levels of fecundity and survival, which is consistent with long-term declines in population numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Precipitation affects vegetative growth, and in turn, food and cover (Campbell 1972, Riley et al 1992, Giesen 2000, Patten et al 2005b. Jackson and DeArment (1963) speculated LPC from the panhandle historically migrated to central Texas (.100 km distance) during winter; however, most documented movements have been 10 km (Campbell 1972, Riley et al 1994, Hagen 2003, Pitman et al 2006b). Range expansion occurs incrementally during fall through natal dispersal (Pitman et al 2006b) and during spring through establishment of new leks by subordinate males when populations are high (Dunn andBraun 1985, Haukos andSmith 1999).…”
Section: Discussionmentioning
confidence: 99%